Glatthaar, Forged in battle - The Civil War alliance of Black soldiers and White officers - Shea, William (Teaching History: A Journal of Methods, 1991)
Many Americans-apparently including at least a few textbook authors-still assume that blacks were essentially passive recipients of emancipation during the Civil War. Joseph Glatthaar’s new book makes it perfectly clear that tens of thousands of blacks played an active and important role not only in the abolition of slavery but also in the preservation of the republic.